Level of knowledge general practitioners about filling medical certificate causes of death at Gunung Jati regional hospital, Cirebon city 2022 - Rusman, Andri Andrian; Taufan, Ali; Haeni, Linlin; Nastiar, Moch Nabil Yazid (Jurnal EduHealth, 2024)
The Medical Certificate of Cause of Death (SMPK) is an official letter that contains the identity of a person and the causes that caused the person to die. The cause of death listed on the SMPK can be used for epidemiology, prevention, and management of certain diseases. Data from the SMPK itself becomes the main data to determine the epidemiology of certain diseases. The format for filling out the medical certificate of the cause of death generally follows the standards issued by the Ministry of Health through BALITBANGKES based on international standards issued by the World Health Organization (WHO). This study aims to determine how the level of knowledge of general practitioners about the medical certificate of the cause of death and its filling in RSDGJ. The research method used in this study is descriptive observational, this research approach is a cross-sectional approach. The sample of this study was a sample that met the inclusion and exclusion criteria using consecutive sampling technique. The sample size in this study was in accordance with total sampling of 42 respondents who worked as general practitioners on duty at Gunung Jati Regional Hospital, Cirebon City. The majority of respondents in this study were female, namely 61.9% with the most age range of 26-35 years by 76.2%. The results of this study showed that most respondents showed a good level of knowledge as much as 66.7%, respondents with sufficient knowledge were 28.6%, and respondents with less knowledge were 4.8%. Based on these results it can be concluded that the level of knowledge of general practitioners at Gunung Jati Regional Hospital, Cirebon City about filling out the Cause of Death Medical Certificate is good.